Development of Physics Learning Media Using IPRO (Interactive Presentation PowerPoint) Animation on the Global Warming Topic - Alifia Rohimatul Azizah; Mita Anggaryani (PendIPA Journal of Science Education, 2021)
IPRO is an interactive presentation learning media using PowerPoint as a learning medium in the form of an application. The meter used in the learning media is global warming. This media presents material in the form of animation that can build interaction between students and digital media.This research aims to produce appropriate and effective digital learning media in physics online learning activities on animation-based global warming material using PowerPoint. The research method used is the development of ADDIE. This study states that the developed IPRO is suitable for studying global warming material with consideration of the validity and effectiveness data results that meet the media category. The  data collection technique used a validation questionnaire the results 90,5% included in the very valid caragory and fit for uses. The effectiveness of high school student learning, which can be proven 87,05% by the mean percentage of respondents who have met the criteria is very valid. Therefore, the IPRO physics learning media that has been developed is suitable for uses in learning.